Measuring the Depth of Character: Religious and Moral Values in Early Childhood - Tania, Agustina (Civiliza Publishing, Indonesia., 2025)
Education is an effort to prepare students for future roles through guidance, teaching, and training. This study aims to assess the depth of character by instilling religious and moral values in early childhood at the Mangunan Experimental Kindergarten located on Jalan Kenanga, Cupuwatu II, Purwomartani, Special Region of Yogyakarta. This study used a descriptive qualitative research method. Data collection was carried out through observation of children's behavior during learning. The behaviors observed were prayer, caring, patience, cooperation, responsibility, and tolerance. The number of subjects studied was 141 children. The data analysis technique used in this study was the Miles and Huberman model, which included data condensation, data display, and data conclusion drawing/verifying. The results showed that teachers had instilled religious and moral values in children properly and correctly. The instillation of these values was carried out in daily learning activities so that what has been taught by teachers can be directly practiced by children. Teaching religious and moral values is not only done in the school environment but also needs to be done in the family and community environment. Therefore, teachers, parents, and the community must support and cooperate with each other in teaching religious and moral values to children. The methods that can be used are role models, habituation, stories, videos and audio visuals.